2022
DOI: 10.3389/fcell.2022.986261
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous visualization of RNA transcripts and proteins in whole-mount mouse preimplantation embryos using single-molecule fluorescence in situ hybridization and immunofluorescence microscopy

Abstract: Whole-mount single-molecule RNA fluorescence in situ hybridization (smRNA FISH) in combination with immunofluorescence (IF) offers great potential to study long non-coding RNAs (lncRNAs): their subcellular localization, their interactions with proteins, and their function. Here, we describe a step-by-step, optimized, and robust protocol that allows detection of multiple RNA transcripts and protein molecules in whole-mount preimplantation mouse embryos. Moreover, to simultaneously detect protein and enable RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…We developed a whole-mount in situ hybridization method with high sensitivity and super-resolution. This method enables analysis of the mRNA accumulation in a simple, convenient and cost-effective manner, compared with section in situ hybridization combined with the TSA system [23] and whole-mount smRNA-FISH with the RNA-scope technique [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a whole-mount in situ hybridization method with high sensitivity and super-resolution. This method enables analysis of the mRNA accumulation in a simple, convenient and cost-effective manner, compared with section in situ hybridization combined with the TSA system [23] and whole-mount smRNA-FISH with the RNA-scope technique [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a single molecule RNA uorescent in situ hybridization (smRNA-FISH) with the RNA-scope technique enables detection of mRNAs in mammalian oocytes and embryos with high sensitivity in whole-mount samples [27][28][29]. In these methods, mRNAs are detected by the hybridization of Z-shaped DNA probes consisting of 50-60 bases, of which 20-25 bases on one side are complementary to sequences of the speci c transcripts and 14 bases on the other side are complementary to pre-ampli er DNA sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule RNA FISH was performed according to the manufacturer’s protocol for the RNAscope® Fluorescent Multiplex Reagent Kit 320850 (ACD #320850), as described previously [45, 46]. Briefly, 5 × 10 4 GSCs were seeded onto laminin-coated coverslips (12 mm) in a 24-well plate for 24 hours to reach 80% confluence, then fixed in freshly prepared 4% paraformaldehyde (PFA) (Electron Microscopy Sciences, 19200).…”
Section: Methodsmentioning
confidence: 99%